A rare case of adult intestinal intussusception: Epithelioid type mesenchymal tumor of the small intestine - Ece DİLEGE and Halil COŞKUN and Cemal KAYA and Uygar DEMİR and Özgür BOSTANCI and Banu YILMAZ and Mehmet MİHMANLI (Turkish Journal of Gastroenterology, 2019)
-